(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to the problems of meaning in linguistic studies, its philosophical and logical interpretation. The main focus is on the issues of meaning on lexical and semantic levels, and their specific realization. The relationship between the word’s and the sentence’s meaning are analyzed with accent on the priority of sentence’s meaning.